Implementation of Pinggan Adintaku Nutrition Education for Elementary School Students - Effendy, Devi Savitri; Tosepu, Ramadhan; Bahar, Hartati; Kohali, Rizki Eka Sakti Octaviani; Rosmini, Rosmini; Suci, Winarzih (Abdi Masyarakat, 2023)
Konawe Regency in the Southeast Sulawesi Province is one of the regions facing a significant burden of malnutrition among school-age children and adolescents. We developed a nutritional education program for schoolchildren in response to this issue. The Pinggan Adintaku nutritional education program combines face-to-face counseling and educational games. The program aims to equip students with knowledge and skills in selecting healthy foods for themselves, with the expectation of significantly impacting their health and academic performance. The primary media used is the Nutrition Diary module, designed to be age-appropriate and culturally relevant to the program's location. The activities occurred from August to September 2023, centered at Bajo Indah Elementary School in the Soropia District of Konawe Regency, Southeast Sulawesi. The participants included 18 individuals, consisting of 17 fifth-grade students and one teacher. Qualitative evaluation results indicate that almost all Pinggan Adintaku nutritional education aspects were effective. However, the Schoolchildren's Nutrition Diary module needs further development by adding topics and narratives to make it a comprehensive and informative resource tailored to the needs of schoolchildren.